Design of Acceleration’s Monitoring System by Computer with Bluetooth Communication to Determine Intensity - Khoirunnisa, Ijabatul; Rakhmadi, Frida Agung; Wibowo, Nugroho Budi (Proceeding International Conference on Science and Engineering, 2017)
Indonesia lies on the junction of three large plates, resulting in frequent occurrence of earthquakes. This research is trying to design a building acceleration monitoring system which the purpose of this research was to create and characterize the acquisition system, to create and test the building acceleration monitoring system by computer with bluetooth communication. This research was conducted in five phases: making the data acquisition system, characterizing of data acquisition system, making monitoring system, data sampling of monitoring system, and data analyzing of monitoring system. The result of this research showed that transfer function and correlation coefficient of data acquisition on each axis was: yx=16,722?0x+0 rx=1 ; yy=16,722?0y+0 ry=1 ; and yz=16,722?0z+0 rz=1. Sensitivity of the acquisition system on each axis was 16,722 bit/gal. Acceleration data of monitoring system has range -0,17944 gal to 0,119628 gal which intensity 0 MMI. Accuracy of earthquake’s monitoring system on x axis was 97,204%, y axis was 97,374%, and z axis was 97,210%.